2015
DOI: 10.1123/jsm.2013-0285
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of International Football Matches on Primary Sponsors and Shareholder Wealth

Abstract: The effect of sponsorship on the stock market returns of the sponsoring companies has been previously studied, but the internationalizing aspect of sponsorship has been overlooked. We examine returns to shareholders for firms sponsoring international football matches using an event study analysis. We find that there are cumulative abnormal returns to stockholders of sponsoring firms of international matches 10 days after the match and 20 days after the match. This finding is robust across several different eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Despite their high profile nature, only a small number of studies have investigated this compelling sponsorship context. Bouchet et al (2015) investigated the potential for 139 shirt sponsorships across the EPL, Italy’s Serie A, Spain’s La Liga and Germany’s Bundesliga to impact the sponsor’s stock price, following its appearance in international matches. The research found that sponsoring firms saw abnormal returns of up to 2.24% 10 days following the match and abnormal returns of up to 5.03% 20 days after the match (Bouchet et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their high profile nature, only a small number of studies have investigated this compelling sponsorship context. Bouchet et al (2015) investigated the potential for 139 shirt sponsorships across the EPL, Italy’s Serie A, Spain’s La Liga and Germany’s Bundesliga to impact the sponsor’s stock price, following its appearance in international matches. The research found that sponsoring firms saw abnormal returns of up to 2.24% 10 days following the match and abnormal returns of up to 5.03% 20 days after the match (Bouchet et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Bouchet et al (2015) investigated the potential for 139 shirt sponsorships across the EPL, Italy’s Serie A, Spain’s La Liga and Germany’s Bundesliga to impact the sponsor’s stock price, following its appearance in international matches. The research found that sponsoring firms saw abnormal returns of up to 2.24% 10 days following the match and abnormal returns of up to 5.03% 20 days after the match (Bouchet et al , 2015). The paper noted that many EPL shirt sponsors seek to provide their brand exposure on a global basis, a goal sought by B2B sponsor Aon via its sponsorship of Manchester United.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sehingga untuk anggaran selama satu musim kompetisi klub sangat mengandalkan pemasukan dari tiket pertandingan kandang (home), sponsorship dan subsidi dari Bandan Liga Indonesia Baru (BLI-B) selaku operator Liga 2 Indonesia 2018. Hasil temuan ini terkait dengan potensi penghasilan utama dari klub sepakbola dalam menjalani kompetisi: (a) pendapatan hari pertandingan melalui kehadiran stadion, (b) hak siar (termasuk distribusi untuk berpartisipasi, dan lolos dalam kompetisi nasional dan internasional), dan (c) pendapatan komersial melalui sponsor (Bouchet, Doellman, Troilo, & Walkup, 2015), sedangkan (Pantuso, 2017) menambahkan bawah faktor merchandising, dan visibilitas media sosial juga berkontribusi. Pada poin terakhir yang diususlkan oleh Pantuso, peneiliti tidak menemukan hal tersebut terjadi Pada PSIM Yogyakarta.…”
Section: Keterbatasan Anggaran Dalam Menjalani Liga 2 Indonesia 2018unclassified
“…Bouchet et al (2015) investigated the potential for 139 shirt sponsorships across the EPL, Italy’s Serie A, Spain’s La Liga and Germany’s Bundesliga to impact the sponsor’s stock price, following its appearance in international matches. The research found that sponsoring firms saw abnormal returns of up to 2.24 percent 10 days following the match, as well as abnormal returns of up to 5.03 percent 20 days after the match (Bouchet et al , 2015). There was not a statistically significant effect of the announcement of the tour on the sponsoring firm’s stock price.…”
Section: Literature Reviewmentioning
confidence: 99%